1999
DOI: 10.1055/s-2008-1043795
|View full text |Cite
|
Sign up to set email alerts
|

Cellular drug resistance in acute myeloid leukemia: literature review and preliminary analysis of an ongoing collaborative study

Abstract: Cellular drug resistance is one of the main causes of the frequent ultimate failure of chemotherapy in childhood acute myeloid leukemia (AML). We here summarize the results of a literature review on in vitro drug resistance in childhood AML, focusing on studies using so-called cell culture assays. We also briefly describe some results of an ongoing collaborative study between the Research Laboratory of Pediatric Oncology in Amsterdam (University Hospital Vrije Universiteit) and the German BFM-AML Group. In gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…They also showed that the in vitro drug resistance profiles of AML M5 samples resembled those in ALL, except that the former are resistant to glucocorticoid. 16 Similarly, we found here that M5 cells were relatively sensitive to L-ASP, and were significantly more resistant to Pred and Dex than were M0, M1, M2, M4 and M7 cells.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…They also showed that the in vitro drug resistance profiles of AML M5 samples resembled those in ALL, except that the former are resistant to glucocorticoid. 16 Similarly, we found here that M5 cells were relatively sensitive to L-ASP, and were significantly more resistant to Pred and Dex than were M0, M1, M2, M4 and M7 cells.…”
Section: Discussionsupporting
confidence: 61%
“…Klumper et al 14 suggested that in vitro resistance to AraC correlated with chemotherapy failures in 29 cases of childhood initial AML. Kaspers et al 16 reported that in a group of 55 samples of newly diagnosed children with AML patients with more than 5% blasts in their BM at day 15 of remission induction chemotherapy had AML cells that were relatively more resistant to DNR, IDA, VP16 and AraC than those of the patients with less than 5% blasts. In adult AML, several studies Correlation between drug sensitivity and FAB classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in vitro drug resistance testing differs considerably from the in vivo situation, it does provide valuable indications as to which factors might be important in drug sensitivity in vivo (Kaspers et al, 1999). hENT1 mRNA expression correlated with sensitivity to ara-C and also seemed to correlate with sensitivity to 2-CdA, DAC and dFdC, indicating that transport across the cell membrane is an important step for deoxynucleoside analogue induced cytotoxicity.…”
Section: Discusssionmentioning
confidence: 99%
“…We and others have already demonstrated the prognostic importance of cellular resistance in childhood leukemias. [21][22][23][24] We previously reported childhood AML to be relatively resistant to a large number of drugs when compared with childhood acute lymphoblastic leukemia (ALL). 25 Also, specific genetic ALL and AML subgroups may show different resistance profiles.…”
Section: Introductionmentioning
confidence: 99%